Pusat Pelatihan Anggar Di Pekanbaru Dengan Pendekatan Arsitektur High Tech - Rafii Pandu Julianda; Mira Dharma Susilawati; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Riau hasn’t have a complete sport facility for fencing. Considering the fact that fencing has plenty achievement on national scale, therefore goverment should have providing a place to held all its activity. Supported by good facilities then all the athletes are expected to be more passioned to do all the training so the achievement could be increased, wether on national scale or even international. Fencing is one of sportive and modern sport. As time goes by, all the equipment and technology on the used building will be developing in no time. For that, the place that can be used for training should be developing as well to keep the pace with current era. Using High Tech as the building’s theme could be seen on the use of glass materials, as well as the building’s bone structure, expressive and modern look and shape gave an appealing vibes on the building.Keywords: Fencing, High Tech, expressive, modern.